URBAN STREAMS OF THE CITY OF CÁCERES-MT, BRAZIL: A LOOK FOR CONSERVATION - Oliveira Junior, Ernandes Sobreira; Buhler, Bárbara Ferraz; Muniz, Claumir Cesar; Furlan, Amabilen Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The urban streams are an important source of natural resources for human populations, but despite of it, suffer from degradation and the indifference of the public and society in general. This study aimed to analyze the physical aspects of the main urban streams in Caceres-MT, municipality considered the gateway to the Pantanal. To this end, streams, previously selected, were observed regarding physical (riparian vegetation, general maintenance, odor, local biota diversity, and surroundings occupation) from the source to the mouth. The streams studied had a high degree of degradation in the whole section (headwaters, middle course and mouth). Only the Fontes mouth was considered natural, without impact. Other streams, Sangradouro, Jose Renato, and Bastos, also the Fontes stream in the middle course, contained large amounts of garbage and very evident signs of eutrophication (macrophytes in abundance). It was concluded that visual observation of the physical aspects of a given natural resource can contribute to the analysis of environment quality, and can provide important data with a view to implement appropriate management plans for the conservation site